2018
DOI: 10.1121/1.5068648
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity-based theory of phase velocity and attenuation of sound in mud consisting of water and flocculated clay particles

Abstract: Recent theory of authors ascribes attenuation in typical marine mud sediments to be caused by viscous interaction of sea water with embedded silt particles. Influence of underlying clay matrix is regarded as passive and of minor importance. Present paper considers silt-less mud where clay particles are flocculated to a card-house structure, with the flocculation hypothesis yielding a porosity of 90%. During the passage of a sound wave, Van-der-Waals forces between platelets cause the matrix to move to-and-fro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been shown that reliable attenuation records are challenging to obtain in mud due to primitive techniques and complication from ambient noise [33]. With limited understanding and measurement of the geoacoustic properties in mud, sediment acoustic modeling is currently an ongoing research topic [34].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that reliable attenuation records are challenging to obtain in mud due to primitive techniques and complication from ambient noise [33]. With limited understanding and measurement of the geoacoustic properties in mud, sediment acoustic modeling is currently an ongoing research topic [34].…”
Section: Introductionmentioning
confidence: 99%